Respiratory Motion Estimation using a 3D Diaphragm Model - Bögel, Marco; Riess, Christian; Maier, Andreas; Hornegger, Joachim; Fahrig, Rebecca (Bildverarbeitung in der Medizin 2014, 2014)
Long acquisition times of several seconds lead to image artifacts in cardiac C-arm CT. These artifacts are mostly caused by respiratory motion. In order to improve image quality, it is important to accurately estimate the breathing motion that occurred during image acquisition. It has been shown that diaphragm motion is correlated to the respiration-induced motion of the heart. We present a method to estimate an accurate three-dimensional (3D) model of the diaphragm and its compression motion field from a set of C-arm CT projection images acquired during free breathing. First results on the digital XCAT phantom are promising. The method is able to estimate the motion field amplitude exactly. The boundaries of the estimated compression motion field are estimated within 3mm accurac
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD5.respir_33